2008
DOI: 10.1021/jp709869f
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Formation of Metal−Molecule−Metal Junctions between Au Nanoparticles As Probed by Surface-Enhanced Raman Spectroscopy

Abstract: Laser power dependent p-aminothiophenol (PATP) adsorption on Au nanoparticles (NPs) has been systematically investigated using surface-enhanced Raman spectroscopy. Molecular junctions (MJs) were found to form between NPs with the quinonoid PATP as the bridge molecule with an external energy provided by the incident laser. The relative Raman intensities of b2 modes to a1 modes increased with the increasing laser power. The abnormal enhancement of b2 modes is most possibly attributed to the laser-induced formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 52 publications
11
70
0
2
Order By: Relevance
“…5b is the SERS signal of MNPR after the capture of p-ATP. The characteristic Raman scattering peak at 1,079 cm À 1 (a 1 band of p-ATP) and three additional peaks at 1,145, 1,383 and 1,436 cm À 1 (b 2 band of DMAB, oxidatively transformed from p-ATP) were observed 28,41,42 . In contrast, after the capture of MG, the characteristic Raman scattering peaks at 1,180, 1,370 and 1,618 cm À 1 were observed 44 .…”
Section: Article Nature Communications | Doi: 101038/ncomms4456mentioning
confidence: 98%
See 1 more Smart Citation
“…5b is the SERS signal of MNPR after the capture of p-ATP. The characteristic Raman scattering peak at 1,079 cm À 1 (a 1 band of p-ATP) and three additional peaks at 1,145, 1,383 and 1,436 cm À 1 (b 2 band of DMAB, oxidatively transformed from p-ATP) were observed 28,41,42 . In contrast, after the capture of MG, the characteristic Raman scattering peaks at 1,180, 1,370 and 1,618 cm À 1 were observed 44 .…”
Section: Article Nature Communications | Doi: 101038/ncomms4456mentioning
confidence: 98%
“…It is noticable that the peak c.a. 1,142 cm À 1 existed with considerable enhancement by -N ¼ N-stratching mode (so called 'b 2 mode') of 4,4 0 -dimercaptoazobenzene (DMAB), which was oxidatevly transformed from p-ATP during SERS measurement 28,41,42 . Raman-mapped images of MNPRs display that the Raman signal of highest Au content (50%) show relatively weaker signal enhancement than samples with lower Au content due to the lack of plasmonic hotspots.…”
Section: Mnpr Frabricationmentioning
confidence: 99%
“…It was demonstrated that the appropriate laser illumination allowed the chemical transformation of PATP to DMAB on Au or Ag nanostructures [32,33]. This reaction was catalyzed by the SPR in air or in the alkaline solution due to the activation of oxygen on noble metal nanoparticles.…”
Section: The Dimerization Of Patp In Pure [Bmim]bfmentioning
confidence: 99%
“…为了进一步确定 PATP 异常 SERS 谱峰的归属, 我们从实验上合成了 DMAB 分子并获得其 SERS 谱图 [98] . DMAB 分子的 [73,98] . 我们首先在低功率密度, 即光谱不随激光照射时间 增加而改变的条件下, 进行 PATP 的电化学 SERS 实验.…”
Section: 强 此现象称为表面增强拉曼光谱(Surface-enhancedunclassified
“…根据 PATP 在银金等金属纳米结构表面转化为 DMAB 的反应与激发光波长 [70,132] 、激发光功率 [98,133] 光照时间 [73,98] 、环境气氛 [134,135] 、溶液酸碱性 [64~67] 等实 验条件的依赖关系, 我们发展了研究等离激元光催化反 应的理论模型, 提出了 PATP 在固气界面和固液界面发 生表面催化偶联反应转化为 DMAB 的反应机理 [136,137] , 如图 9 所示. 等离激元纳米结构上的光催化反应与传统 半导体材料上的光催化反应最大的区别是, 等离激元纳 米结构通过 SPR 对可见光具有高效的吸收, 并且通过非 辐射弛豫产生能级高于金属费米能级的"热电子"及能 级低于金属费米能级的"热"空穴.…”
Section: 反应机理unclassified